Ethnicity and low wage traps: favouritism, homosocial reproduction and economic marginalization. (December 2017) - Hudson, Maria; Netto, Gina; Noon, Mike; Sosenko, Filip; de Lima, Philomena; Kamenou-Aigbekaen, Nicolina
This article analyses the relationship between cultural difference, social connections and opportunity structures using interview evidence from low-paid workers and managers in local government, the health service, facilities management and housing. Exploring the operation of homosocial reproduction it reveals the double-edged nature of informality and the role of favouritism in particular in perpetuating ethnic advantage and privilege. While demonstrating that uses of homosocial reproduction need to be sensitive to intersections of identities or categories of difference, the article adds further evidence of the persistent gap between equal opportunities policies and practice for ethnic minorities in the United Kingdom labour market. The article concludes that stronger forms of positive action, and even positive discrimination, are needed to address the low pay traps and restricted opportunities of ethnic minority workers.